1996
DOI: 10.1346/ccmn.1996.0440104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Citric Acid and Glycine on the Adsorption of Mercury (II) by Kaolinite under Various pH Conditions

Abstract: Abstract--This investigation was carried out to study the effect of different concentrations of citric acid and glycine, which are common in freshwaters, on the kinetics of the adsorption of Hg by kaolinite under various pH conditions. The data indicate that Hg adsorption by kaolinite at different concentrations of citric acid and glycine obeyed multiple first order kinetics. In the absence of the organic acids, the rate constants of the initial fast process were 46 to 75 times faster than those of the slow ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
29
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 23 publications
(14 reference statements)
7
29
0
1
Order By: Relevance
“…26 However, it is often incorrect to apply simple kinetic models such as first-or second-order rate equations to a sorption system with solid surfaces that are rarely homogeneous and because the effects of transport phenomena and chemical reactions are often experimentally inseparable. 27 Singh et al 28 reported that the sorption of mercury(II) by kaolinite obeyed multiple first-order kinetics. Almost all the kinetic systems reported in the literature for metal ion sorption have only been subjected to pseudo-first-order model analysis.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, it is often incorrect to apply simple kinetic models such as first-or second-order rate equations to a sorption system with solid surfaces that are rarely homogeneous and because the effects of transport phenomena and chemical reactions are often experimentally inseparable. 27 Singh et al 28 reported that the sorption of mercury(II) by kaolinite obeyed multiple first-order kinetics. Almost all the kinetic systems reported in the literature for metal ion sorption have only been subjected to pseudo-first-order model analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Organic and inorganic pollutants (e.g., large organic molecules such as atrazine and heavy metals such as Cd, Pb, and Hg) can easily exchange for innocuous elements, such as Ca or Na, from the interlayer of the expandable clay minerals. The intermolecular interactions of organic pollutants with clay-mineral surfaces are expected to be crucial in chemical/biological transformations, transportation, and retention of these contaminants (e.g., Inskeep and Baham, 1983;Siantar et al, 1994;Singh et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Glycine is an organic ligand commonly present in natural water systems and it may enhance the rate of heavy metal adsorption by kaolinite and montmorillonite (Singh et al, 1996). Barrie et al (1993) and Gyani (1994) studied the complexation of cadmium with glycine.…”
Section: Introductionmentioning
confidence: 99%
“…It can also affect Hg transformation through other processes (e.g., Hg(II) binding to organic matter (see Benoit et al 2001and Haitzer et al 2002 and photoredox (see Mauclair et al 2008;Nriagu 1994;Zhang 2006;Zhang and Lindberg 1999;and references therein)). Numerous studies have been reported on adsorption of Hg(II) by various particles, e.g., clay minerals (Hamilton et al 1995;Sarkar et al 2000;Singh et al 1996), oxides (Bonnissel-Gissinger et al 1999;Gunneriuson and Sjoberg 1993;Gunneriuson et al 1995;Sarkar et al 1999;Thanabalasingam and Pickering 1985;Tiffreau et al 1995;Walcarius et al 1999;Weerasooriya et al 2006Weerasooriya et al , 2007, and soils (Schluter 2000;Schuster 1991;Yin et al 1996;Yin et al 1997a, b). Desorption of Hg(II) from particles has also received attention (Arias et al 2004;Yin et al 1997b), yet the literature in this regard has remained limited.…”
mentioning
confidence: 99%
“…In natural waters as well soils, solid particles co-exist with natural organic matter (NOM) and both interact with Hg(II) species. A competition thus occurs between particles and NOM for binding Hg(II) (Arias et al 2004;Singh et al 1996). NOM can also bind to particles (Johnson et al 2004;Schuster 1991) and affect Hg(II) distribution between particles and solutions.…”
mentioning
confidence: 99%